A study of maintenance management on government building: Ministry of Youth and Sport / Fathurozi Tukimon - Tukimon, Fathurozi (Faculty of Architecture, Planning and Surveying, 2009)
The preparation of this dissertation was mainly motivated by the desire to provide an overview of maintenance management on government building practice in Malaysia.. The study has specific aim and objectives to achieve in the end. The primary aim of this study is identify the maintenance management system on the selected building. The second objective is to determine the problem occur by observation. The last objective is to identify the satisfy level of building user on selected building by questionnaire. This dissertation includes the outlines of the introduction to the subjects and each sub topic, and also explained elaborate about the building types in Malaysia characteristic of government building in Malaysia and the legislation implementation to government building in Malaysia. Research methodology which had been applied in the three (3) case studies are through observations to the building overview, interviewing relates person of the three government building and make a questionnaire to the building user which are focus on staff. Form analysis it can be find that the maintenance management system on government building at three case study, the major problem on those three case study building which is parking area and several defect on structure and the user satisfaction of the building facilities and conditions that overally are in good condition. Finally, conclusion from the research findings and development of recommendations for future improvement on government building selected and other building related.